2015
DOI: 10.1016/j.molcel.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Function of CDK7 in Transcription by Virtue of a Recently Described TFIIH Kinase Inhibitor

Abstract: In this issue of Molecular Cell, Nilson et al. (2015) took advantage of THZ1, a recently described covalent inhibitor of the TFIIH kinase CDK7, to further characterize the role of this enzyme in the early stages of transcription and postprocessing events. They unveiled an unexpected function of CDK7 in RNA polymerase II pausing and mRNA capping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…10). Currently, several laboratories are developing inhibitors of cyclin-dependent kinases (CDK) that have a critical role in regulating transcription initiation, pause release, and elongation (e.g., CDK7, CDK8, or CDK9), the three main steps involved in RNA synthesis (11,12). Other approaches are inhibition of DNA repair mechanisms (e.g., irinotecan, topotecan, olaparib; ref.…”
Section: Introductionmentioning
confidence: 99%
“…10). Currently, several laboratories are developing inhibitors of cyclin-dependent kinases (CDK) that have a critical role in regulating transcription initiation, pause release, and elongation (e.g., CDK7, CDK8, or CDK9), the three main steps involved in RNA synthesis (11,12). Other approaches are inhibition of DNA repair mechanisms (e.g., irinotecan, topotecan, olaparib; ref.…”
Section: Introductionmentioning
confidence: 99%
“…However, THZ1-induced inhibition of IEG transcription in this study may not be solely attributable to defects in RNAPII stalling. Using an in vitro transcription system with Hela nuclear extract (Nilson et al, 2015 ) demonstrated that THZ1 not only causes defects in RNAPII CTD phosphorylation and promoter proximal stalling, but also in co-transcriptional capping and productive elongation, meanwhile with minimal effects on transcription initiation, thus revealed unexpected function of Cdk7 in RNAPII stalling and mRNA capping (Coin and Egly, 2015 ). It is interesting to examine whether the above regulatory machinery is conserved in post-mitotic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…These events facilitate the release of the RNA Pol II and activate the productive elongation phase of transcription ( Figure 1C) (Adelman and Lis, 2012;Jonkers and Lis, 2015). Furthermore, CDK9-dependent phosphorylations play a key role in the recruitment of the 3'end processing and splicing factors, responsible for messenger RNA (mRNA) maturation (Yang et al, 2005;Coin and Egly, 2015).…”
Section: How Cdk9 Workmentioning
confidence: 99%